Mild phenotype associated with an interstitial deletion of the long arm of chromosome 1. Issue 12 (December 1998) - Melis, D; Perone, L; Sperandeo, M P; Sabbatino, M S; Tuzzi, M R; Romano, A; Parenti, G; Andria, G
Abstract : We report on a 21 month old child referred to us because of facial dysmorphism and psychomotor retardation. The patient's phenotype was characterised by a wide and receding forehead, broad nasal bridge, redundant retronuchal skin, low set and poorly shaped ears, micrognathia, and small hands and feet. High resolution R and G banding karyotype analysis of peripheral blood lymphocytes showed an interstitial deletion of the long arm of chromosome 1 spanning bands q22 to q24. The cytogenetic results were confirmed by molecular analysis. The phenotype observed in our patient was relatively milder than those reported in other patients with an interstitial deletion of chromosome 1q.